2003
DOI: 10.1271/bbb.67.2683
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution and Intracellular Localization of Catechins in Tea Leaves

Abstract: We investigated the leaf tissue and cellular morphology of tea (Camellia sinensis). Osmiophilic material, presumably catechins, was present in mesophyll cells, but not in epidermal cells. Electron microscopy showed that catechins were localized to restricted regions within the central vacuoles. In addition, two kinds of small vacuoles of 0.5-3 microm were present in mesophyll cells. One vacuole had catechins within its whole lumen, while the other had an electron-lucent lumen. We found fusion profiles between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 1 publication
0
26
0
Order By: Relevance
“…However, studies of the localization of catechins in tea-leaf tissues have been contradictory. Suzuki et al (2003) showed that catechins are mainly localized in the vacuoles of mesophyll cells, and not in epidermal cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies of the localization of catechins in tea-leaf tissues have been contradictory. Suzuki et al (2003) showed that catechins are mainly localized in the vacuoles of mesophyll cells, and not in epidermal cells.…”
Section: Resultsmentioning
confidence: 99%
“…The enzymes responsible for this step are polyphenol oxidase (PPO) and peroxidase (POD), which are also situated in the tea leaves but spatially separated from the polyphenolic constituents, which are stored in micrometer sized compartments. 4 When flavanols and enzymes get into contact, e.g., after crushing of the leaves and disruption of the internal cell structures, the 3′,4′-hydroxyl groups of the polyphenolic B-rings are oxidized to their corresponding o-quinones, which are then subject to further reactions. This step leads initially to dimeric flavanols with presently four generic structures established: theaflavins 7−10 ( Figure 2), theacitrins, theasinensins, and theanaphthoquinones.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Deng et al (2001) demonstrated that Realgar with a smaller particle size of 150 or 100 nm markedly reduced cell viability through apoptosis compared with that with a particle size of 200 or 500 nm. Suzuki et al (2003) demonstrated that synthesized catechins were localized to restricted regions within the large central vacuoles (5-15 lm) or some small vacuoles (0.5-3 lm) in tea leaf mesophyll cells. It is conceivable that catechin form complexes with metal ions such as Ca(II) and Mg(II) and special proteins in central vacuole.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that catechin form complexes with metal ions such as Ca(II) and Mg(II) and special proteins in central vacuole. Suzuki et al (2003) supposed that synthesized catechins in ER or Golgi apparatus are packed in the formation of a small vacuole and small vacuoles fuse with each other and as a result, catechins are transported into the large central vacuole. However, localization of individual catechin was not fully elucidated.…”
Section: Discussionmentioning
confidence: 99%